Association between coffee intake and skeletal muscle mass among U.S. adults: a population-based study - Yin, Huangyi; Zhu, Wei; Guo, Liuqing; Li, Weishan; Liang, Min (Frontiers in Nutrition, 2024)
A limited number of studies have reported that the possible effects of coffee intake on skeletal muscle mass, but the results have been inconsistently conclusive and there are no large sample studies concerning the U.S. population. Therefore, the purpose of our study was to explore the connection between coffee consumption and skeletal muscle mass in U.S. adults.The population for this cross-sectional study was drawn from the National Health and Nutrition Examination Survey (NHANES) from 2011-2018. Appendicular lean mass was accurately obtained from DXA, and skeletal muscle mass was assessed using appendicular skeletal muscle mass adjusted for body mass index (ASMBMI). Coffee and caffeine consumptions were obtained on a 24-hour dietary recall questionnaire. Furthermore, the associations between coffee and caffeine intake and skeletal muscle mass were evaluated using three multiple linear regression models and smoothed curve fitting. Subgroup analyses based on age, gender, ethnicity and body mass index (BMI) were performed to assess the robustness of these relationships.This cross-sectional survey included a total of 8333 participants. After adjusting for all covariates, higher intake of coffee, caffeinated coffee, and caffeine was associated with elevated ASMBMI (coffee: β =0.01, 95% CI:0.01, 0.02, P-value <0.001; caffeinated coffee: β =0.01, 95% CI:0.01, 0.02, P-value <0.001; caffeine: β =0.02, 95% CI:0.01, 0.04, P-value <0.001). Meanwhile, smoothed curve fitting showed that coffee, caffeinated coffee, and caffeine intake were linearly and positively associated with ASMBMI. After further stratification by sex, age, and ethnicity, the positive relationships between coffee (especially caffeinated coffee) and caffeine intake and ASMBMI were not modified (P for interaction >0.05). However, these relationships disappeared when the BMI over 30 kg/m 2 .In general, consumption of coffee and caffeine is positively associated with skeletal muscle mass. Therefore, an appropriate increase in coffee and caffeine intake may be advocated in populations at high risk for low skeletal muscle mass.